Effect of Tinutuan Tinu Key Complementary Feeding on the Nutritional Status of Infants Aged 6-12 Months - Solang, Sesca D.; Langi, Grace K.L.; Lumy, Freike S.N. (Poltekkes Kemenkes Palu, 2024)
Introduction: One of the problems often experienced by children related to the fulfillment of nutrition that has a negative impact on child growth and development is stunting. This study aims to analyze the effect of Tinutuan Tinu Key complementary feeding on the nutritional status of infants aged 6-12 months. Methods: This experimental study without a control group was conducted in Wori Village, North Minahasa Regency. The study population was all babies born to pregnant women who were respondents in the first year of the study , namely mothers who were pregnant throughout 2023, and continued in the second year, namely babies born at the end of 2023-2024, totaling 52 babies. The intervention was carried out for 14 days to the babies. Complementary foods were prepared by health cadres. Babies and mothers received assistance from health workers 14 times. The main variable in this study was the nutritional status of the baby Results: The results of the study showed that the average nutritional status of toddlers based on body length according to age before the intervention of providing complementary foods was 2.67%, and after intervention by 3.13% with a significance value (2-tailed) of 0.004. Statistical analysis using paired sample t-test to see the difference in the average between the two samples and the results obtained p value <0.005 which means that the provision of MP-ASI there is a difference in the average body length before and after the intervention. Conclusion: The Tinutuan tinu key complementary feeding potentially affects the nutritional status of children during their growth period, if children's food intake is met properly, then the child's growth and development will be good and they will be free from nutritional problems